(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
This study was carried out to determine the distribution of the weeds in two important cash crops of Pakistan along with their distribution pattern in research area. Total of 56 weed species was recorded belonging to 23 plant families by the quadrat method with random sampling in wheat and potato fields of seven different villages from Tehsil Sharqpur Sharif, Punjab, Pakistan. A multivariate technique, Two Way Indicator Species Analysis (TWINSPAN), using PC-ORD (Version-6.22) classified the weeds into groups and associations. The dominant weed communities were Cichorium-Euphorbia- Cyperus community, Chenopodium-Digera-Fumaria weed community, Poa- Chenopodium-Coronopus weed community, Parthenium-Euphorbia-Veronica weed community, Euphorbia-Achyranthes-Brassica community and Setaria-Polypogon- Solanum community. Phytodiversity of weeds found in this study, remarkably indicated the variable distribution pattern of weeds in both the crop fields. Moreover, communities of weeds emerged can be helpful in better planning of the weed management in crop fields. Bangladesh J. Plant Taxon. 28(1): 233-240, 2021 (June)